References about “The Dictionary of Economic Terms” in 6 languages (Confluenţe Bibliologice, 2013)
“The Dictionary of Economic Terms” in 6 languages is elaborated in Polyglot Dictionary of Project International Scientiﬁc  Research Terms.
Keywords: book launch